Motivasi Keagamaan Mahasiswi Pendidikan Agama Islam Universitas Negeri Jakarta dalam Menggunakan Busana Syar’i: Analisis Tindakan Sosial Max Weber - Taqiyyah; Muhamad Ridwan Effendi (Advances In Education Journal, 2025)
The use of syar’i attire has become increasingly prominent in the daily lives of female students of Islamic Religious Education at Universitas Negeri Jakarta, reflecting changes in religious practice within the campus environment. This study aims to examine the meaning of syar’i dress, identify students’ motivations for wearing it, and analyze the types of social action underlying this practice based on Max Weber’s theory. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. The data were analyzed thematically using Weber’s classification of social action. The findings indicate that the motivation for wearing syar’i attire is rooted in strong religious understanding and reinforced by psychological, social, and emotional factors. Weberian analysis reveals that value-rational action is the most dominant type, supported by goal-rational, traditional, and affective actions. These findings highlight syar’i dress as a meaningful social practice that reflects the internalization of religious values in students’ academic and social lives.